The Pathophysiology and Treatment of Hypertension in Patients With Cushing's Syndrome - Barbot, Mattia; Ceccato, Filippo; Scaroni, Carla (Frontiers in Endocrinology, 2019)
When hypertension, a pathology that is frequently found in the general population, presents in a young patient, secondary causes such as Cushing’s syndrome (CS), a rare disease characterized by long-term elevated cortisol levels, should be considered. Present in approximately 80% of CS patients independently of their age and sex, hypertension is one of the pathology’s most prevalent, alarming features. Its severity is principally associated with the duration and intensity of elevated cortisol levels. Prompt diagnosis and rapid initiation of treatment are important for reducing/delaying the consequences of hypercortisolism. Glucocorticoid excess leads to hypertension via a variety of mechanisms including mineralocorticoid mimetic activity, alterations in peripheral and renovascular resistance, and vascular remodelling. As hypertension in CS patients is caused by cortisol excess, treating the underlying pathology generally contributes to reducing blood pressure (BP) levels, although hypertension tends to persist in approximately 30% of cured patients. Surgical removal of the pituitary tumor remains the first-line treatment for both adrenocorticotropin hormone (ACTH) dependent and independent forms of the syndrome. In light of the fact that surgery is not always successful in curing the underlying disease, it is essential that other treatments be considered and prescribed as needed. This article discusses the mechanisms involved in the pathogenesis of CS and the pros and the cons of the various antihypertensive agents that are presently available to treat these patients.